A SARS-CoV-2 RBD vaccine fused to the chemokine MIP-3α elicits sustained murine antibody responses over 12 months and enhanced lung T-cell responses - Gordy, James Tristan; Hui, Yinan; Schill, Courtney; Wang, Tianyin; Chen, Fengyixin; Fessler, Kaitlyn; Meza, Jacob; Li, Yangchen; Taylor, Alannah D.; Bates, Rowan E.; Karakousis, Petros C.; Pekosz, Andrew; et al. (Frontiers in Immunology, 2024)
Background: Previous studies have demonstrated enhanced efficacy of vaccine formulations that incorporate the chemokine macrophage inflammatory protein 3α (MIP-3α) to direct vaccine antigens to immature dendritic cells. To address the reduction in vaccine efficacy associated with mutation in SARS-CoV-2 mutants, we have examined the ability of receptor binding domain vaccines incorporating MIP-3α to sustain higher concentrations of antibody when administered IM and to more effectively elicit lung T cell responses when administered intranasally.Methods: 6-8 week old Balb/c mice were immunized intramuscularly or intranasally with DNA vaccine constructs consisting of the SARS-CoV-2 receptor binding domain alone or fused to the chemokine macrophage inflammatory protein 3α (MIP-3α). In a small scale (n=3/group) experiment, mice immunized IM with electroporation were followed for serum antibody concentrations over a period of one year and for bronchoalveolar antibody levels at the termination of the study. Following IN immunization with unencapsulated plasmid DNA (n=6/group), mice were evaluated at 11 weeks for serum antibody concentrations, quantities of T cells in the lungs, and IFNγ-and TNFα-expressing antigen-specific T cells in the lungs and spleen. Results: At 12 months post primary vaccination, recipients of IM vaccine incorporating MIP-3α had significantly, approximately three-fold, higher serum antibody concentrations than recipients of vaccine not incorporating MIP-3α. Area under the curve analyses of the 12-month observation interval demonstrated significantly greater antibody concentrations over time in recipients of the MIP-3α vaccine formulation. At 12 months post primary immunization, only recipients of the fusion vaccine had concentrations of serum neutralizing activity deemed to be effective. After intranasal immunization, only recipients of the MIP-3α vaccine formulations developed T-cell responses in the lungs significantly above those of PBS controls. Low levels of serum antibody responses were obtained following IN immunization. Conclusions: Although requiring separate IM and IN immunizations for optimal immunization, incorporating MIP-3α in a SARS-CoV-2 vaccine construct demonstrated the potential of a stable and easily produced vaccine formulation to provide the extended antibody and T-cell responses that may be required for protection in the setting of emerging SARS-CoV-2 variants. Without electroporation, simple, uncoated plasmid DNA incorporating MIP-3α administered intranasally elicited lung T cell responses.